Implementasi Aplikasi Point Of Sales Berbasis Android Untuk Kedai Kopi Kuale - Uro Abdurohim; Meidi Fransisca Siregar; Muhammad Anim Hunaifi (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
Kedai Kopi Kuale is a business engaged in the culinary field located on Jl. Sultan Hasanudin No.55, Patunas, Tungkal Ilir District, West Tanjung Jabung Regency, Jambi. At this time Kuale Coffee still uses a conventional system for ordering food or drinks where the waiter uses pen and paper as a medium to record orders from customers. The service system is less effective and efficient along with the increasing number of customers. This causes customers to have to wait for a menu availability report from the waiter where the waiter still has to reconfirm to the kitchen to report menu orders and check menu availability. Android-based Point of sale application is a point of sale application that was built using the waterfall Software Development Life Cycle (SDLC) medote which has 6 stages including System Engineering, Analysis, Design, Coding, Testing and Maintenance. This method is done by looking at and analyzing problems using the Unified Modeling Language (UML). Then designing a solution in the form of an information system website wireframe, if completed, then enter the Coding stage or build a system using the PHP programming language and the Laravel framework. Then testing to users and then maintenance as an evaluation for further development using the User Acceptance Test (UAT) method. This application gets the expected results. The functions run well and are well received by the users.